Analisis dan Implementasi Pemikiran Pendidikan Islam Imam Suproyogo - Mahendra, Yusri Yusra; Ondeng, Syarifuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Imam Suprayogo's Islamic educational thinking is centered on the idea that religious and general knowledge must be activated to produce people who are not only intellectually intelligent, but also spiritually and morally strong. This thinking is very relevant as we face the challenges of modernity and globalization because it offers solutions to the broad educational needs that include intellectual, emotional, and spiritual aspects. The purpose of this article is to study Imam Suprayogo's thinking on Islamic education and find out how it can be applied in the education system in Indonesia. This study investigates the basic concepts underlying Islamic education according to Suprayogo. These concepts include the importance of integrating religious and general knowledge, the formation of Islamic character, and the development of critical thinking in the context of Islamic values. This study uses a qualitative approach. It is hoped that the application of these ideas will produce a generation that is not only knowledgeable, but also has strong morality, is competitive, and is able to face the challenges that come in its time.